When floodplain restoration meets socio‐ecological goals for rural stormwater management - Lisa A. Peterson; Patricia M. Awerbuch; Sabrina Spatari (Journal of Industrial Ecology, 2025)
Floodplain restoration is an approved stormwater management method, but rarely chosen by developers due to the perceived high cost and lengthy approvals required from regulatory agencies. Yet, when chosen, restoring a floodplain yields significant environmental benefits for the community due to improved flood resiliency and wetland habitat and superior reduction of negative externalities. In 2012, a corporation in Lancaster County, Pennsylvania, explored the option to restore a historic floodplain on its 40‐hectare property to fulfill the stormwater management requirements for a planned development project. There was a social dynamic at play in this instance that allowed the developer, municipality, and citizens to achieve a win across three dimensions often in conflict: maximizing private economic returns, achieving environmental compliance, and benefiting the community ecologically. Using a social–ecological system (SES) framework, this paper analyzes the course of the development project through the government approvals process and the actual restoration of the floodplain. Two influential actors are identified who do not often appear in the literature on SESs: sports advocacy groups and religious groups. We posit that the developer's industry was uniquely receptive to conservation appeals and that the proximity of an urban metropolis made collective action a relevant strategy for the region. Critical factors in the decision process were the cost–benefit analysis contracted by the developer, local (county) government leadership, and a history of local citizen activism. We conclude that a misalignment of anthropogenic and ecological boundaries can prevent such positive outcomes and that collective action is a viable strategy to overcome that challenge.